Excel 2010 made simple - Katz, Abbott (Made simple., 2011)
Learn all the key features, understand what's new, and utilize dozens of time-saving tips and tricks. This is a practical and highly effective approach to using Excel 2010, showing you the best way to complete the most common spreadsheet tasks.